ANALISA KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI DESA BAKARAN BATU KECAMATAN LUBUK PAKAM - P, Ilma Hamdalah; Sarifah, Jupriah; Lubis, Marwan; Harahap, Rumilla (Buletin Utama Teknik, 2024)
Clean water is one of the basic needs to support human life. As the years go by, the population and infrastructure in Bakaran Batu Village, Lubuk Pakam District, increase, with the increase in population and infrastructure in Bakaran Batu Village, Lubuk Pakam District, there will definitely be an increase in users. clean water.In this research, an analysis of the availability of clean water was carried out in Bakaran Batu Village, Lubuk Pakam District. This research aims to determine the clean water needs of the people of Bakaran Batu Village, Lubuk Pakam District until 2033 so that it can be used as a reference for further research. In this research, the method used is a quantitative method with population data for the last 10 years whose calculations were carried out using arithmetic, geometry and least square selected based on the correlation coefficient and standard deviation requirements, and the results of clean water needs based on existing secondary data and comparing them with the availability of existing clean water sources, predicted clean water needs for the Bakaran Batu Village area, Lubuk Pakam District with calculations using the projection method. used to project population growth for the next 10 years.From the results of the analysis, it was found that the need for clean water in the Bakaran Batu Village service unit, Lubuk Pakam District in 2033, which refers to the predicted population growth, is 8.52 liters/second, while the availability of clean water is 11 liters/second to meet existing water needs.